"Man a Kill a Man for Nutin": Gang Transnationalism, Masculinities, and Violence in Belize City. (August 2021) - Baird, Adam
Belize has one of the highest homicide rates in the world; however, the gangs at the heart of this violence have rarely been studied. Using a masculinities lens and original empirical data, this article explores how Blood and Crip "gang transnationalism" from the United States of America flourished in Belize City. Gang transnationalism is understood as a "transnational masculinity" that makes cultural connections between local settings of urban exclusion. On one hand, social terrains in Belize City generated masculine vulnerabilities to the foreign gang as an identity package with the power to reconfigure positions of subordination; on the other, the establishment of male gang practices with a distinct hegemonic shape, galvanized violence and a patriarchy of the streets in already marginalized communities. This article adds a new body of work on gangs in Belize, and gang transnationalism, whilst contributing to theoretical discussions around the global to local dynamics of hegemonic masculinities discussed by Connell and Messerschmidt (2005) and Messerschmidt (2018).